2009
DOI: 10.1136/ard.2009.109447
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility variants for rheumatoid arthritis in the TRAF1-C5 and 6q23 loci: a meta-analysis

Abstract: Genetic markers in the 6q23 region and TRAF1-C5 are associated with rheumatoid arthritis, in particular with positive anti-CCP and RF profile. With the exception of rs6920220, which shows highly consistent results, other proposed markers have high between-study heterogeneity that may reflect unrecognised phenotypic or genetic variability (eg, gene environment interactions) within rheumatoid arthritis. Furthermore, these markers may not be the true causative loci but rather be in linkage disequilibrium with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
0
21
0
2
Order By: Relevance
“…The above result was indirectly supported by Viatte S et al in anti-CCP antibody negative patients [32]. Recent results in Caucasian RA patients have demonstrated that the TNFAIP3 variant led to an increased risk of RA in a negative anti-CCP antibody and RF-positive patients compared with a positive anti-CCP antibody and RF negative patients [33,34]. The presence of ACA can reflect the functionality of inflammatory endothelial cells and the tendency toward thrombosis, and some RA patients may harbor ACA.…”
Section: The Association Between Single Nucleotide Polymorphisms In Tmentioning
confidence: 73%
“…The above result was indirectly supported by Viatte S et al in anti-CCP antibody negative patients [32]. Recent results in Caucasian RA patients have demonstrated that the TNFAIP3 variant led to an increased risk of RA in a negative anti-CCP antibody and RF-positive patients compared with a positive anti-CCP antibody and RF negative patients [33,34]. The presence of ACA can reflect the functionality of inflammatory endothelial cells and the tendency toward thrombosis, and some RA patients may harbor ACA.…”
Section: The Association Between Single Nucleotide Polymorphisms In Tmentioning
confidence: 73%
“…rs6920220 is consistently associated with rheumatoid arthritis (RA) risk [228], and the results for other polymorphisms of the TRAF1 gene in relation to this disease are contradictory. The A allele of the rs10818488 polymorphism may correlate with a higher risk of SLE [229].…”
Section: Tnf Receptor-associated Factor (Traf1-traf6) Gene Polymorphimentioning
confidence: 99%
“…[87][88][89][90][91][92] Specifically, a study of 3962 RA patients and 3531 healthy controls demonstrated strong association (OR = 1.2; 95% CI: 1.1-1.3; P = 2.6 × 10 -6 ) with a variant (rs6920220) in an intergenic region of chromosome 6q23 region between oligodendrocyte linear transcription factor 3 (OLIG3) and TNF-α-induced protein 3 (TNFAIP3). 91 The validity of this study has been confirmed by a recent metaanalysis of seven studies investigating the association of the TNFAIP3-OLIG3 region with RA, which indicated a strong association of the variant rs6920220 (OR = 1.2, 95% CI: 1.2-1.3; P = 7.9 × 10 -17 ).…”
Section: Tnfaip3-olig3 Is Associated With Ra Pathogenesismentioning
confidence: 99%
“…91 The validity of this study has been confirmed by a recent metaanalysis of seven studies investigating the association of the TNFAIP3-OLIG3 region with RA, which indicated a strong association of the variant rs6920220 (OR = 1.2, 95% CI: 1.2-1.3; P = 7.9 × 10 -17 ). 92 Since the TNFAIP3 gene acts as a negative regulator of the transcription factor nuclear factor-κB (NFκB) in response to TNF-and toll-like receptor activation, 93,94 it is an attractive RA susceptibility candidate gene. Unfortunately, currently there is no therapeutic agent specifically targeting this molecule.…”
Section: Tnfaip3-olig3 Is Associated With Ra Pathogenesismentioning
confidence: 99%